2022
DOI: 10.3390/nu14102152
|View full text |Cite
|
Sign up to set email alerts
|

Cannabidiol and Cannabidiol Metabolites: Pharmacokinetics, Interaction with Food, and Influence on Liver Function

Abstract: Cannabidiol (CBD) is widely available and marketed as having therapeutic properties. Over-the-counter CBD is unregulated, many of the therapeutic claims lack scientific support, and controversy exists as to the safety of CBD-liver interaction. The study aims were to compare the pharmacokinetics of commercial CBD and CBD metabolites following the ingestion of five different CBD formulations, determine the influence of CBD on food induced thermogenesis, determine the influence of food on CBD pharmacokinetics, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 62 publications
4
27
0
Order By: Relevance
“…Abbotts et al 73 examined the pharmacokinetics of five different oral CBD formulations each dosed at 30 mg in healthy participants. The water‐soluble CBD formulations containing various excipients (sorbitol, gum arabic, or maltodextrin) attained much greater plasma concentrations of CBD and metabolites than standard formulations, such as medium chain triglyceride oil or CBD as a crystalline powder.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Abbotts et al 73 examined the pharmacokinetics of five different oral CBD formulations each dosed at 30 mg in healthy participants. The water‐soluble CBD formulations containing various excipients (sorbitol, gum arabic, or maltodextrin) attained much greater plasma concentrations of CBD and metabolites than standard formulations, such as medium chain triglyceride oil or CBD as a crystalline powder.…”
Section: Resultsmentioning
confidence: 99%
“… 94 Pharmacovigilance of liver enzymes may be required even at low CBD doses, as we identified one study in which elevated liver enzymes were observed in four out of 59 participants following repeated oral dosing with 300 mg CBD. 55 However, in a more recent study, a single dose of 30 mg CBD did not affect liver enzymes, 73 highlighting lower doses may be of less concern. Future studies are needed to assess liver function following repeated lower doses.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…In both cases, however, the safety of using CBD as a therapeutic agent must also be considered. In this context, recent studies have shown that CBD is not harmful to metabolism and liver functions when used at low doses [ 117 ]. Together with this, the need to use CBD in long-term therapy, such as e.g.…”
Section: The Modulatory Activity Of Cannabidiol With Respect To the N...mentioning
confidence: 99%
“…While liposomes and liposomal drugs tend to accumulate in the liver after intravenous administration, this may increase hepatic injury or hepatotoxicity and result in safety issues, such as when the encapsulated drug itself had hepatotoxicity, as did many chemotherapeutics. Fortunately, as an FDA-approved medicine, CBD has very good tolerance; so far, there has been no report about significant hepatotoxicity or obvious liver injury for CBD [ 48 , 49 ]. Meanwhile, PPD shows no hepatoxicity either [ 50 ].…”
Section: Introductionmentioning
confidence: 99%